Peningkatan Kemampuan Berpikir Kritis dan Disposisi Matematis Siswa SMP dengan Menggunakan Pendekatan Problem Posing - Rifaatul Mahmuzah; M. Ikhsan; Yusrizal Yusrizal (Universitas Syiah Kuala, 2014)
One of the goals of learning mathematics in school is to improve the ability of problem solving, the student was required to have a higher thinking skills such as critical thinking skills. Use of appropriate critical thinking skills will greatly assist students in improving problem-solving abilities. In addition to critical thinking, another very important aspect to be improved in mathematics learning is positive views of students towards mathematics or known as mathematical disposition. Problem posing approach that requires students to ask questions and make the settlement is expected to be able to develop students 'thinking skills, especially critical thinking skills and mathematical change students' views of mathematics became more positive. This study aims to assess the improvement of critical thinking skills and dispositions that are taught to students' mathematical problem posing approach and students are taught with conventional teaching. This study is a design experiment using pre-test post-test control group design. The population in this study is the seventh grade students of SMP Negeri 9 Banda Aceh in the school year 2012-2013. Samples were taken two classes VII3 class as the experimental class and the class as a class VII4 control through random sampling technique. The instrument used to obtain research data is test critical thinking skills questionnaire sheet-scale mathematical and mathematical disposition. The statistical test used to analyze the data increase critical thinking skills and dispositions are mathematically ANOVA test two paths. The results showed that an increase in critical thinking skills and dispositions that are taught to students' mathematical problem posing approach better than students taught with conventional teaching.